Alternative Text Pre-Processing using Chat GPT Open AI - Indri Tri Julianto; Dede Kurniadi; Yosep Septiana; Ade Sutedi (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2023)
Text Pre-Processing is the first step in Sentiment Analysis. Categorizing a sentiment in a dataset is part of the Text-Preprocessing stage to get the optimal model accuracy value. Generative Pretrained Transformer, often known as Chat GPT, is a Machine Learning model that can automatically generate realistic and meaningful text. This study aims to examine the capability of GPT Chat as an alternative in the Text-Pre-Processing stage by utilizing GPT Chat 3 from the openai.com website in the Text-Pre-Processing stage of the collected tweet data. The data used in this research is the result of crawling Twitter by inserting the keyword